Preanalytical stability of HIV-1 and HCV RNA: impact of storage and plasma separation from cells on blood donation testing by NAT - Schulze, Torsten; Weiß, Christel; Luhm, J.; Brockmann, C.; Görg, S.; Hennig, H. (Transfusion medicine, 2011)
Background: The aim of this study was to evaluate the optimal preanalytical conditions prior to nucleic acid amplification technology (NAT) for human immunodeficiency virus-1 (HIV-1) or Hepatitis C virus (HCV) RNA in pools of 96 plasma specimens with regard to storage temperature, time and plasma separation in a blood donation environment. Study design and methods: Changes in viral nucleic acid concentration of HIV-1 and HCV were observed for 5 days according to the Paul-Ehrlich-Institute's (PEI) guidelines that demand 95%-detection limit of at least 10 000 IU mL−1 for HIV-1 RNA and 5000 IU mL−1 for HCV RNA within a single donor blood specimen. Ninety-five per cent detection limits of HIV-1 RNA over 3 days after storage at either 5 or 21 °C were evaluated by using standardised HIV-1 RNA-positive plasma. Results: HCV RNA in whole blood samples proved to be more stable than HIV-1 RNA. Whole blood storage at 21 °C was shown to decrease the detectability of HIV-1 RNA even after only 18 h. Plasma samples once used for NAT at time 18 h did not alter viral stability up to 48 h after donation. Ninety-five per cent detection limits of HIV-1 RNA were securely below 10 000 IU mL−1 for 24 h after whole blood storage at 5 °C. Conclusions: These results may lead to a discussion around the most suitable preanalytical conditions in blood donation environments. Contrary to the current PEI guidelines that allow storage of whole blood specimens up to 18 h at 21 °C, these results suggest that immediate storage in a 5 °C container after blood donation is more suitable and would permit storage of whole blood up to 24 h prior to the separation of plasma from cells.